2020
DOI: 10.3390/ijerph17186461
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Moderates Negative Outcome from Stress during the COVID-19 Pandemic: A Moderated-Mediation Approach

Abstract: Resilience refers to an individual’s healthy coping abilities when encountering adverse life events. The COVID-19 pandemic represents a situation with a high amount of stress exposure, which in turn may be associated with negative emotional outcome like depressive symptoms. The current study investigated if resilience moderated the effect of stress on symptoms of depression and if anxiety symptoms mediated this association. An adult sample of community controls completed the Perceived stress scale 14 (PSS-14),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
104
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 52 publications
16
104
1
2
Order By: Relevance
“…Resilience could be a factor that shaped psychological reactions of the examined Hungarian adults. Havnen et al [ 51 ] found that Norvegian adults in March 2020 during the COVID-19 pandemic high on resilience reported lower levels of perceived stress, depression, and anxiety. Resilience can be described as a healthy adaptation despite adversity, and it involves of a group of factors which contribute to healthy coping and health promotion [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience could be a factor that shaped psychological reactions of the examined Hungarian adults. Havnen et al [ 51 ] found that Norvegian adults in March 2020 during the COVID-19 pandemic high on resilience reported lower levels of perceived stress, depression, and anxiety. Resilience can be described as a healthy adaptation despite adversity, and it involves of a group of factors which contribute to healthy coping and health promotion [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Havnen et al [ 51 ] found that Norvegian adults in March 2020 during the COVID-19 pandemic high on resilience reported lower levels of perceived stress, depression, and anxiety. Resilience can be described as a healthy adaptation despite adversity, and it involves of a group of factors which contribute to healthy coping and health promotion [ 51 ]. Havnen et al [ 51 ] emphasized that people high on resilience were less affected by negative emotional reactions (such as increased worry and anxiety) due to the experience of stress during the coronavirus pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A study during a previous viral outbreak found that among patients who survived the Severe Acute Respiratory Syndrome (SARS) epidemic, natural soundscapes may have differentiated restorative effects depending on the level of stress [34]. The outbreak of COVID-19 has created relatively new forms of stressors for mental health [35]. Recent research proved that stress raised during the COVID-19 pandemic could recovery from simpler virtual exposure to forest environments with combined audio and visual stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…These adolescents are at risk of suffering from posttraumatic stress disorder (PTSD), depression, anxiety, disruptive behaviors, and substance abuse ( McLaughlin and Lambert, 1970 ). Especially in times of the coronavirus disease 2019 (COVID-19) there is high prevalence of psychological distress in adolescents (e.g., Havnen et al, 2020 ; Prime et al, 2020 ; Ran et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%